HUBUNGAN TINGKAT KECEMASAN DENGAN SIKLUS MENSTRUASI PADA SISWI SMK N 07 BATAM - Perdoman, Acholder Tahi; Asda, Andi; Izzaturrahmah, Tilfi (Universitas Batam, 2023)
Background: : Menstruation is uterine bleeding that occurs cyclically and is experienced by most women of reproductive age. The menstrual cycle has a significant relationship with hormonal changes that occur in the body. One of the things that can affect the menstrual cycle is psychological conditions such as depression and anxiety. Methods: This research method is observational analytic with a cross sectional approach which was carried out at SMK N 07 Batam City in June 2023. The sampling technique in this study used the nonprobability sampling method with a quota sampling technique with a sample size of 193 respondents. This research was conducted by collecting questionnaire data. Data analysis used the Spearman's Rho test. Results: The results of the research on 193 respondents showed a significant relationship between anxiety levels and the menstrual cycle in female students at SMK N 07 Batam in 2023. From the results of the Spearman rho test, a p-value of 0.002 was obtained and an r-value of 0.168 so that Ho was rejected and Ha was accepted. Conclusion: Based on the results of this study it can be concluded that there is a significant relationship between anxiety levels and the menstrual cycle in students of SMK N 07 Batam in 2023.